Evaluation of the Efficiency of Interparticle Interactions in Nanosystems - Hanna O. Demchenko; Natalia M. Rusinchuk (Journal of Nanotechnology)
Wide range of applications of nanoparticles causes the need to study their properties, and the influence of the interparticle interaction on the formation of the nanosystem properties is a well-known experimental phenomenon. The aim of this work is to study the influence of interparticle interactions on the properties of nanosystems theoretically. The influence of the interparticle interaction was simulated based on the near-field interaction potential and local field distribution. The local field distribution in the system was calculated using the Green function method and the concept of the effective susceptibility. The results show that interaction between nanoparticles can be neglected if the distance between them is bigger than the critical one. Expressions for evaluation of the efficiency of the interparticle coupling were proposed and compared with the existing experimental results. The results of the simulation are in good agreement with the measured values of the critical interparticle distance. The approach may be useful for simulation of interactions in the system of many nanoparticles and for engineering of nanostructures for different applications.